Princípios globais de contabilidade gerencial: relação com os estágios do ciclo de vida das empresas de capital aberto listadas na Brasil, Bolsa, Balcão (B3) - Batista, Tiago Nunes (2019)
The objective of this paper was to analyze the relationships of the Global Management Accounting Principles (GMAP) with the stages of the organizational life cycle (OLC) of the publicly traded companies listed on Brazil, Bolsa e Balcão (B3). The sample analyzed comprised 207 companies from 2010 to 2017 and a total of 1656 observations. To answer the research problem, the methodology consisted of constructing an index of adequacy to the recommendations proposed by the GMAP (IGMAP) and identifying OLC stages based on Dickinson's model (2011), and the relationship between these variables analyzed by means of regression model estimation. The technique used was panel data and the model chosen was the Ordinary Least Squares (OLS). GMAP. The results show that there is a positive relationship for the intermediate cycles of growth and maturity and negative for the others. The regression analysis of the general model and stratified by sector was more robust when analyzed with OLC control, confirming the relationship between the IGMAP and the stages of the life cycle. The sectors with the highest and lowest adherence to GMAP were the Public Utility (78.99%) and Financial (51.74%) sectors, respectively. It is noteworthy that in eight years, the research period, 95.65% of the companies went through more than one stage and 62.32% of them went through at least 3 (three) distinct stages, showing that the OLC is not linear and it does not due to the deterministic aspect of the time variable. Moreover, it was evident that the average compliance with the Principles increased in the analysis period as a whole, reaching 30%, and when comparing the ex-ante (2010-2013) and ex-post (2014-2017) averages to the publication of the PGCG, the ex-post period averages were higher for all sectors with significant samples for analysis.